1994
DOI: 10.1111/j.1439-0507.1994.tb00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of fluconazole‐amphotericin B antagonism to Candida albicans by agar diffusion

Abstract: Fluconazole is a bis-triazole antifungal which partly antagonizes the activity of amphotericin B against Candida albicans (and other Candida species). This antagonism can easily be demonstrated by radial agar diffusion. Amphotericin B at reservoir concentrations of up to 1.2 mg l-1 showed a diffusion behaviour which was described by means of a simple mathematical analysis. Therefore quantitative determination of the antagonism was possible. Using a reference strain of Candida albicans, the critical concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In contrast, antagonism was reported when low concentrations of each agent were used against C. parapsilosis and indifference was observed when higher concentrations of both ketoconazole and flucytosine were employed (19). (107,122,154,185,186,198,214). Most of these studies have been performed using C. albicans isolates, but results with the non-albicans Candida spp.…”
Section: Neoformans (I) In Vitro Datamentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, antagonism was reported when low concentrations of each agent were used against C. parapsilosis and indifference was observed when higher concentrations of both ketoconazole and flucytosine were employed (19). (107,122,154,185,186,198,214). Most of these studies have been performed using C. albicans isolates, but results with the non-albicans Candida spp.…”
Section: Neoformans (I) In Vitro Datamentioning
confidence: 84%
“…Antagonism among antifungal agents might occur in one of several ways. (i) Direct antifungal action at the same site results in decreased ability of other agents to exert their competitive effects on that site or at an altered target, as proposed for the azoles and amphotericin B (31,49,182,183,185,186,203). Azoles block the synthesis of ergosterol in the fungal cell membrane and may thus render amphotericin B inactive, since this agent exerts its activity by binding to ergosterol in the cell membrane.…”
Section: Mechanisms Of Interactions For the Antifungal Agentsmentioning
confidence: 99%
“…The effectiveness of treatment with the combination of amphotericin B with azole for Candida infection has not been determined and is still controversial. Fluconazole and amphotericin B have been shown to be antagonistic against C. albicans under carefully selected in vitro conditions [36]. An in vivo study by Sugar et al [37], however, did not demonstrate this antagonism against C. albicans.…”
Section: Discussionmentioning
confidence: 97%
“…During this time, both antagonism and synergism of the activity of AMB when fungi are pre-exposed to azoles have been observed in vivo as well as in vitro [20]. The resulting data are, however, confusing, with reports ranging from antagonism [23][24][25][26], through additive or synergistic effects [27,28], to no effect [23,29]. In clinical terms, the development of combined drug regimens and the antagonism conferred upon otherwise fungicidal concentrations of AMB seen in C. albicans pre-exposed to FLZ is disconcerting [30,31].…”
Section: Introductionmentioning
confidence: 82%
“…A quantitative agar double-diffusion method used to study this antagonism has shown that FLZ antagonizes the effect of AMB against C. albicans [24]. Another group of researchers observed that AMB and FLZ interactions with C. albicans were antagonistic [47].…”
Section: Discussionmentioning
confidence: 99%